A Paradigms and Theories of Career Development in Technology and Vocational Education and Training (TVET) - Andi Putra; M Giatman; Nurhasan Syah; Zulkifli Zulkifli (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
echnical and Vocational Education and Training (TVET) faces fundamental challenges in preparing learners to navigate an increasingly non-linear and disruptive digital career landscape. This study critically analyzes classical and contemporary career development theories within a constructivist paradigm framework and formulates their implications for TVET career guidance in the Industry 4.0 and 5.0 era. A systematic literature review with critical-conceptual analysis using an adapted PRISMA protocol was employed. The findings reveal that classical theories by Super, Holland, Srebalus et al., Osipow, and Herr and Cramer retain fundamental value; however, their positivistic assumptions are insufficient to address the complexity of digital-era careers. The constructivist paradigm, manifested in Savickas' Career Construction Theory and Lent, Brown, and Hackett's Social Cognitive Career Theory, offers more relevant perspectives by positioning individuals as active agents in constructing career meaning. This article proposes the Integrative Career Guidance Model for TVE in the Digital Era (ICGM-Digital), built upon three pillars: constructivist foundation, adaptive competency development, and systemic contextualization, as a practical framework for TVE institutions in designing holistic and adaptive career guidance programs.